ANALISIS PENGARUH STRATEGI PEMASARAN BERBASIS PRINSIP SYARI’AH PADA MASA PANDEMI COVID-19 TERHADAP KEPUTUSAN PEMBELIAN CUSTOMER (STUDI KASUS PADA CV. MJK GLOBAL PANGKALPINANG) - Saputra, Jodi; Ruben Manullang, Rizal; Tri Setyo Mulyani, Hendarti (Jurnal Progresif Manajemen Bisnis, 2022)
This research is motivated by a decrease in furniture sales at CV. MJK Global Pangkalpinang during the Covid-19 pandemic using sharia principles. This decline in sales indicates a customer's purchase decision on furniture products so that it can be formulated in this study that how consumers make purchasing decisions on CV. MJK Global during the Covid-19 pandemic by using sharia principles with a 4p marketing strategy, namely product, price, place and promotion. This study aims to analyze the effect of marketing strategies based on sharia principles during the Covid-19 pandemic on customer purchasing decisions, a case study on CV. MJK Global Pangkalpinang This study uses a quantitative descriptive method, while the sample in this study was 60 respondents. The sampling technique uses certain considerations and criteria by using a questionnaire. The results showed that only the Place variable based on the comparison results where t-count 5.258 > t-table 1.673 significant value 0.001 <0.05, it can be concluded that the place variable has a partially significant influence during the Covid-19 pandemic by using sharia principles on purchasing decisions. Meanwhile, product, price and promotion variables do not have a significant influence on consumer decisions during the COVID-19 pandemic using sharia principles because the t-count is smaller (<) than the t-table and the value is significantly greater (>) than 0.05. While the results of the F test or simultaneously F-count 33,281 > F-table 2.54, it can be concluded that the independent variable has a simultaneous influence on the dependent variable during the covid-19 pandemic using sharia principles.